Биология каштановой минирующей моли, Cameraria ohridella (Lepidoptera, Gracillariidae), в Украине. Сообщение 2 - Акимов, И.А.; Зерова, М.Д.; Нарольский, Н.Б.; Никитенко, Г.Н.; Свиридов, С.В.; Коханец, А.М.; Бабидорич, М.М. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
Приведены данные по биологии и фенологии каштановой минирующей моли в

Украине в 2003—2005 гг. Обсуждаются особенности фенологии 4 генераций

каштановой минирующей моли и особенности зимовки вредителя в полевых

условиях. Приведены фенологические таблицы для каждой генерации вредителя,

фенограммы развития каштановой моли в условиях Киева, а также таблица и

диграмма, характеризующие количественное соотношение различных стадий

развития моли при уходе на зимовку. New data about biology and phenology of the horse chestnut leaf-miner
since May 2003 till the end of May 2005 are given. Phenological

peculiarities of the four generations of
the horse chestnut leaf-mining moth as well as the results of the

hibernation of this pest are discussed.
A calculation of the amount of the effective temperatures from the

beginning of the moth flight and also
the terms of the development of the leaf-miner in the season-2004 are

represented. Phenological tables
for the each generation of the about mentioned pest along with the

phenogram reflected the development
of the horse chestnut leaf-mining moth together with the table and diagram,

wich are characteristic of
quantitative correlation of the different phases of the leaf-miner before

its going to the hibernation, are
made for the first time as adaptable to Koiv natural environment.